Pengaruh Pelatihan, Motivasi dan Kompensasi terhadap Kinerja Karyawan pada PT. Sianso Sukses Sejahtera - Daniel Sibagariang; Sri Wahyuningsih (Departement of Mathematics Education, 2023)
This study aims to determine: 1) the effect of training on employee performance at PT.Sianso Sukses Sejahtera, 2) the effect of motivation on employee performance at PT.Sianso Sukses Sejahtera, 3) the effect of compensation on employee performance at PT.Sianso Sukses Sejahtera, 4) the effect of training, compensation and motivation on employee performance at PT.Sianso Sukses Sejahetera. The population of this research is 70 people. Data collection techniques using a questionnaire. Data analysis was used with multiple linear regression. The results of this study indicate that there is an influence between training, compensation and motivation on employee performance at PT. Sianso Sukses Sejahtera, because t count (32.463) is greater than t table (2.052) so that H1 is accepted. Then training and motivation have a very strong positive influence (r value of 0.235) and have an influence contribution of 59% on employee performance at PT.Sianso Sukses Sejahtera. While the remaining 41% is influenced by other factors.